Flanders in the 21st century: A region in a federal state or a confederation state? (Economic and Political Thought, 2015)
From 1970 to 2014, the Kingdom of Belgium introduced six reforms ofthe political system, which resulted in its change from a unitary state intoa federal one and is undergoing evolution. The country divisions are based onlinguistic and cultural differences. The Kingdom of Belgium is still a constitutionalmonarchy but it consists of three regions, three communities and fourlanguage regions. Each region and community elects its local parliament andthe Federal Parliament at the federal level, which is composed of the Houseof Representatives and the Senate. The latest reform changed the principlesof the functioning of the Senate: the number of senators was raised to 60and they are appointed (nominated and co-opted). Belgium’s political scenereflects the historical conflict of interest between Dutch-speaking Flandersand French-speaking Wallonia. The New Flemish Alliance led by a charismaticpolitician and a republican Bert de Wever has been gaining importancesince 2004. The party slogans call for maximum autonomy for Flanders andfinally the creation of a confederation of Flanders and Wallonia, if the latteragreed. The N-VA reports spectacular successes in local and federal elections.The article aims to analyse the reasons of the present development ofthe situation in the Kingdom of Belgium and to outline the direction thatdynamically developing Flanders determines for the country.